Teknik Mengelola Sampah Berbasis Tumah Tangga - Budiyono, Sri; Suranto, Much; Nugroho, Arif Julianto Sri; Darmo, Pujo; Selfiana, Husna (Journal of Dedicators Community, 2022)
The service was held on Sundays, 25 October 2020, 01 November 2020, 08 November 2020, and 15 November 2020, each of which consists of two sessions, namely 13.00-15.00 (session 1) and continued in session 2, at 15.00 - 17.00 WIB aims to 1) provide knowledge to residents about the nature of waste, both in terms of form, form, and at the same time its dangers; 2) how to handle waste in a professional manner, starting from the statement that used goods are converted into quality goods 3) how to do business using waste vehicles; turning trash into blessed fortune. The method used in achieving the goal is 1) training which is manifested in providing material in theory, 2) giving practice until after training, 3) giving examples of business and marketing. The results of this service are: 1) increased insight of the citizens about the understanding of the nature of waste, both in terms of function, purpose and danger; 2) understand how to solve it; and 3) understand how to do business with garbage type. Overall, the outcome of this service has been achieved, although not all participant who have received training have practiced it.